Rising atmospheric CH4 concentration may have significantly influenced the increase in CH4 uptake by forest soils in China (2010–2020) - Meng Yang (Ecological Indicators, 2025)
As the largest terrestrial carbon sink, forests also play a crucial role in CH4 uptake. China is experiencing various global changes, but their impacts on forest CH4 uptake are unclear. Using a random frest model, this study evaluated the CH4 uptake by forest soils in China from 2010 to 2020 and identified the primary drivers behind the interannual trend in CH4 uptake, focusing on environmental changes such as temperature, precipitation, nitrogen deposition, atmospheric CH4 concentration, and land cover change. The results indicated an average CH4 uptake rate of 0.30 ± 0.04 g CH4 m−2 yr−1, with significant spatial variability. The total regional uptake doubled from 2010 to 2020, reaching an average of 0.80 Tg CH4 yr−1. In addition to forests’ role in fixing CO2, the CH4 consumption by forest soil further enhances their contribution to global warming mitigation. Atmospheric CH4 concentration emerged as the most influential factor, driving a 84.3 % increase in uptake. Notably, compared to the amount of CH4 released into the atmosphere, the concurrent increase in CH4 uptake by forest soil was limited. In specific regions, particularly in semi-arid and nitrogen-deficient environments, water conditions and nitrogen deposition surpassed atmospheric CH4 concentration as the dominant drivers. In contrast, temperature and land cover changes had minor effects. This research provides critical insights into the role of Chinese forests in methane dynamics and contributes to a broader understanding of terrestrial methane fluxes under changing environmental conditions. As the first study to quantify the impact of rising atmospheric CH4 concentrations on CH4 uptake by forest soils in China, it emphasizes the importance of incorporating atmospheric CH4 concentration into regional and global models, a factor that has been lacking in some recent studies.